Do Tourists Willing to Pay for the Value of Environmental Conservation? A Case of Annah Rais Longhouse and Hot Springs - Kamri, Thalany; Kasuma, Jati; Kutok, Justina; Darma, Dio Caisar (Journal of Tourism Management Research, 2020)
There is a need to protect the good nature, environment, and the culture of Bidayuh ethnic in the setting of Annah Rais Longhouse and Hot Springs. In order to manage Annah Rais Longhouse and Hot Springs for long term sustainability, the study on economic valuation is necessary. This is to understand the importance of environmental conservation value. This study seeks to determine visitor’s willingness to pay for conservation fees in Annah Rais Longhouse and Hot Springs, at Kota Padawan, Sarawak. The data were obtained from questionnaires handed out to a 330 visitor who visited Annah Rais Longhouse and Hot Springs. The results revealed that the non-Malaysian visitors’ average willingness to pay was RM14.12 per visit and the local visitors’ average willingness to pay was RM5.49 per visit for environmental conservation. The results of this study can benefit the Sarawak Tourism Board to determine the appropriate addition to the entrance fee at Annah Rais Longhouse and Hot Springs. Hence, encouraging appropriate conservation activities to protect the environment and the culture of Bidayuh ethnic.